PENGARUH SUBSTITUSI STONE ASH AND RICE HUSK ASH TERHADAP KUAT TEKAN BETON - abdi nasrullah; Tarmizi Tarmizi; Heri Wijaya (Jurnal Ilmiah BERING, 2023)
Concrete has become a common choice as a structural material in construction projects. In civil engineering, there are two types of aggregates used as fillers: coarse aggregates such as gravel or crushed stone, and fine aggregates such as sand. Water and cement are used as binding materials in concrete. In order to enhance the compressive strength of concrete beyond the desired target and evaluate the effectiveness of using stone dust and rice husk ash, variations were made by adding 10% stone dust, 10% rice husk ash, and a mixture of 5% stone dust and 5% rice husk ash as partial replacements for cement. Cubic test specimens were formed and used to test the compressive strength at the ages of 3, 14, and 28 days. The test results showed that at 28 days, the average compressive strength of normal concrete was 32.09 MPa, the compressive strength of concrete with 10% stone dust was 32.64 MPa, the compressive strength of concrete with 10% rice husk ash was 22.84 MPa, and the compressive strength of concrete with a mixture of 5% stone dust and 5% rice husk ash was 19.33 MPa. Therefore, the addition of 10% stone dust resulted in higher compressive strength of concrete than the planned target.